Shape of external auditory meatus in north-west Indian crania - Kanta, Suresh; Deswal, Shelja; Dhall, Usha (International Journal of Research in Medical Sciences, 2017)
Background: Skeletal non-metric variables are widely used for population studies. Genetic factors and the usefulness of non-metric traits in population studies were studied by many workers. One of the non-metric traits (shape of external auditory meatus) was studied in present study. Methods: For the study 148 skulls (113 males, 35 females) were used. The crania were retrieved in the Department of Anatomy, Pt. B.D. Sharma PGIMS Rohtak, India. The current investigation will focus on the shape of external auditory meatus. Results: Shape of external auditory meatus was oval /ellipse in most of the cases in North West Indian crania. Oval/ellipse shape of external auditory meatus (EAM) was almost equally distributed (48.13% and 47.80% respectively) followed by round shape (4.07%). No statistically significant bilateral asymmetry was found in present series. Conclusions: Present study has reflected that in addition to caucasoid and negroid features, crania of present series have some resemblance with mongoloid too because of oval/ellipse shape of EAM. Study of shape of meatus will help in racial identification in medico legal cases.